Recycler les rebuts textiles. Organisation et savoir-faire dans le tri de la fripe à Lomé (Togo) - Sylvie Ayimpam (EchoGéo)
Based on ethnographic research, this article explores the organization of work and the expertise of workers in second-hand clothing sorting facilities in Lomé, Togo, the final link in global textile recycling networks. It demonstrates how these workers, despite precarious and informal working conditions, develop specialized skills in categorizing and valorising textile waste into marketable products. The article highlights a fundamental tension between global narratives that promote circular economies as ecological solutions and the harsh realities of the “dirty work” involved in textile sorting, which exposes socio-economic exploitation and "waste colonialism" dynamics. By situating the case of Lomé within a comparative framework, the article contributes to understanding structural inequalities in the textile recycling sector and challenges the promises of a green economy when faced with the realities of precarious labour.